New paradigms in business research - Abdul Rashid, Md Zabid (Universiti Utara Malaysia, 1986)
This paper examined the nature of research business management, the problems in defining research in business, the clues form existing theory of research, and proposed a framework for defining research in business. The nature of research in business covers a wide scope, and is interrelated to sociology, psychology, political science, mathemathics, economics and other sciences. The problems in defining research in business relates to basic versus applied research, the field of study, the place to study, the method, theories and concepts, and the levels of research quantitative versus qualitative research. From the existing theory of research, the author proposed that research in business may be redefined on the basis of three dimensions: the field of study, the methodology, and the theories and concepts. Eight typologies of research and advanced: case study, pure research, transfer, instrumental research, theoretical research, theoretical transfer research, instrumental transfer research, and theoretical instrumental research. Implications of the proposed model are presented.